New Environment, New Invaders—Repeated Horizontal Transfer of LINEs to Sea Snakes. (6th October 2020) - Galbraith, James D.; Ludington, Alastair J.; Suh, Alexander; Sanders, Kate L.; Adelson, David L.
Abstract: Although numerous studies have found horizontal transposon transfer (HTT) to be widespread across metazoans, few have focused on HTT in marine ecosystems. To investigate potential recent HTTs into marine species, we searched for novel repetitive elements in sea snakes, a group of elapids which transitioned to a marine habitat at most 18 Ma. Our analysis uncovered repeated HTTs into sea snakes following their marine transition. The seven subfamilies of horizontally transferred LINE retrotransposons we identified in the olive sea snake ( Aipysurus laevis ) are transcribed, and hence are likely still active and expanding across the genome. A search of 600 metazoan genomes found all seven were absent from other amniotes, including terrestrial elapids, with the most similar LINEs present in fish and marine invertebrates. The one exception was a similar LINE found in sea kraits, a lineage of amphibious elapids which independently transitioned to a marine environment 25 Ma. Our finding of repeated horizontal transfer events into marine snakes greatly expands past findings that the marine environment promotes the transfer of transposons. Transposons are drivers of evolution as sources of genomic sequence and hence genomic novelty. We identified 13 candidate genes for HTT-induced adaptive change based on internal or neighboring HTT LINE insertions. One of these, ADCY4, is of particular interest as a part of the KEGG adaptation pathway "Circadian Entrainment." This provides evidence of the ecological interactions between species influencing evolution of metazoans not only through specific selection pressures, but also by contributing novel genomic material.